The contemporary postfeminist dystopia: disruptions and hopeful gestures in Suzanne Collins' The Hunger Games. Issue 1 (July 2017) - Ruthven, Andrea
Abstract Through an analysis of Suzanne Collins'The Hunger Games trilogy (2008, 2009, 2010), this text will consider the ways in which contemporary postfeminism can be read as a dystopic narrative. The protagonist of the novel (and the rest of the trilogy) is Katniss Everdeen, a young woman who through an ethics of care, disruption of the heteronormative script, and a critical posthuman embodiment offers an alternative to the dystopic present offered by postfeminism. In Katniss' dystopian world, Collins constructs a narrative that highlights the continued need for a feminist politics of engagement and activism that works against claims for neo-liberal individualism.